2018
DOI: 10.1186/s12884-017-1638-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of unplanned out-of-hospital births attended by paramedics

Abstract: BackgroundOver the previous two decades the incidence and number of unplanned out of hospital births Victoria has increased. As the only out of hospital emergency care providers in Victoria, paramedics would provide care for women having birth emergencies in the community. However, there is a lack of research about the involvement of paramedics provide for these women and their newborns. This research reports the clinical profile of a 1-year sample caseload of births attended by a state-wide ambulance service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 27 publications
5
36
0
1
Order By: Relevance
“…All the women were multiparous, without any context of maternal or fetal pathology. As described by us and McLelland et al [23], most of the births (79%) occurred between the hours of 20.00 and 08.00 [24]. Moreover, Flanagan et al reported in a retrospective analysis of 192 unplanned out-of-hospital births, that 21% of the newborns had an Apgar score scored ≤7 out of 10, whereas in our cohort, it represented only 14% of the newborns [25].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…All the women were multiparous, without any context of maternal or fetal pathology. As described by us and McLelland et al [23], most of the births (79%) occurred between the hours of 20.00 and 08.00 [24]. Moreover, Flanagan et al reported in a retrospective analysis of 192 unplanned out-of-hospital births, that 21% of the newborns had an Apgar score scored ≤7 out of 10, whereas in our cohort, it represented only 14% of the newborns [25].…”
Section: Discussionsupporting
confidence: 55%
“…Similarly to our study, most of the births (88.3%) were uncomplicated births in multiparous women. Obstetric complications included postpartum hemorrhage (6.5%), breech (1.3%), cord prolapse (0.6%), and prematurity (11%) [23]. Scott and Esen reported 14 cases of unplanned out of hospital births, which occurred over a three-year period, with a reported incidence of 0.31% [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another Norwegian study found a 50% increased risk of eclampsia/HEELP in nulliparous women living more than 1 hr away from the hospital, underlining how reduced availability may delay or complicate the identification of obstetric emergencies (Engjom et al, ). One Australian study examining the details in 4,096 maternity‐related cases reports various obstetric complications in relation to out‐of‐hospital care, such as postpartum haemorrhage, breech position, cord prolapse, prematurity and neonatal death (McLelland et al, ). Even though adverse outcomes might be rare, these studies underline how unidentified obstetric complications could constitute a great risk to women affected.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, 344 infants were registered born unplanned outside institutions in Norway: this included 152 unplanned home births, 171 births en route to hospital, 16 births in unknown locations and five births in institutions without maternity care services (Medical Birth Registry of Norway, ). Unplanned births outside institutions include all accidental out‐of‐hospital births and are often dealt with by emergency medical technicians (EMTs) without assistance from midwives or physicians (Dietsch, Shackleton, Davies, Alston, & McLeod, ; McLelland, McKenna, Morgans, & Smith, ; McLelland, Morgans, & McKenna, ; Thornton & Dahlen, ). Reasons for the increasing number of out‐of‐hospital births have been attributed centralisation of care (Engjom, Morken, Høydahl, Norheim, & Klungsøyr, ) and midwives acting as gatekeepers of the labour ward (Eri, Blystad, Gjengedal, & Blaaka, ; Vik, Haukeland, & Dahl, ).…”
Section: Introductionmentioning
confidence: 99%